دارالامان لاہور میں خواتین کے حقوق کی صورتحال اور اسلامی تعلیمات کی روشنی میں اصلاحی پہلو: The situation of women’s rights in Darul Aman Lahore and the reformist aspects in the light of Islamic teaching - Dr. Shazia,; Kashaf-ul-Duja, (Al-Amīr Research Journal for Islamic Studies, 2025)
This research study explores the situation of women’s rights in Dar-ul-Aman Lahore, with a special focus on the challenges and opportunities faced by women residing in shelter homes. It highlights the social, legal, and psychological issues that affect women’s empowerment and well-being in this context. Furthermore, the study analyzes these conditions in the light of Islamic teachings, emphasizing the guiding principles of dignity, protection, justice, and social welfare provided by Islam. By linking contemporary realities with religious values, the research suggests reformative measures aimed at improving the protection, rehabilitation, and empowerment of women in Dar-ul-Aman. Keywords: Women’s rights, Dar-ul-Aman Lahore, Islamic teachings, social reform, protection, empowerment, rehabilitation, justice.